Gene Expression Profiles of Circular RNAs and MicroRNAs in Chronic Rhinosinusitis With Nasal Polyps - Yu, Jieqing; Kang, Xue; Xiong, Yuanping; Luo, Qing; Dai, Daofeng; Ye, Jing (Frontiers in Molecular Biosciences, 2021)
Abstract Introduction: CRSwNP is a significant public health problem with a considerable socioeconomic burden. Previous research reported that the pathophysiology of CRSwNP is a complex, multifactorial disease. The function of miRNAs in various diseases, including CRSwNP, is a research hotspot. In contrast, there have been no studies on circRNAs in CRSwNP. Overall, little is known about the functions of circRNAs and miRNAs in CRSwNP. This study aimed to investigate the expression of circRNAs and miRNAs to determine whether these molecules are related to the occurrence and development of CRSwNP. Methods: Nine nasal mucosa samples were collected, namely, 3 ECRSwNP, 3 non-ECRSwNP, and 3 control, for microarray analysis of circRNA and microRNA expression. All of the tissue samples were from patients who were undergoing functional endoscopic sinus surgery in our department. Then we selected some differentially expressed miRNAs and circRNAs for qPCR verification. Receiver operating characteristic (ROC) curve analysis and principal component analysis (PCA) were performed to confirm these molecules are involved in the ocurrence and development of CRSwNP. Results: In total, 2875 circRNAs showed significant differential expression in the CRSwNP group. Specifically, 1794 circRNAs were down-regulated and 1081 circRNAs were up-regulated. In the CRSwNP group, the expression of 192 miRNAs was significantly down-regulated.Through qRT-PCR verification, the expression profiles of hsa-circ-0031593, hsa-circ-0031594, hsa-miR-132-3p, hsa-miR-145-5p, hsa-miR-146a-5p, and hsa-miR-27b-3p were shown to have statistical differences. In addition, ROC curve analysis showed that the molecules with the two highest AUCs were hsa-circ-0031593 with AUC 0.8353 and hsa-miR-145-5p with AUC 0.8690. Through PCA with the six ncRNAs, the first principal component explained variance ratio was 98.87%. The AUC of the six ncRNAs was 0.8657. Conclusions:In our study, the expression profiles of ECRSwNP and non-ECRSwNP had no statistical differences. The differentially expressed circRNAs and miRNAs between CRSwNP and control may play important roles in the pathogenesis of CRSwNP. Altered expression of hsa-circ-0031593 and hsa-miR-145-5p have the strongest evidence for involvement in the occurrence and development of CRSwNP because their AUCs are higher than the other molecules tested in this study. Keywords: chronic rhinosinusitis with nasal polyps, circular RNA, microRNA, bioinformatics array, gene expression profile